CCD-PHOTOMETRY OF CATACLYSMIC VARIABLE ES DRA IN 2001 - Baklanov, A. V.; Pavlenko, E. P.; Dudka, O. I. (Одеські астрономічні публікації, 2017)
On the base of our 34-day photometry of ES Dra we found its ∼ 20 d light variations with amplitude of 1m.6 and suggest this star could belong to the nova-like subclass of cataclysmic variable stars.